2015
DOI: 10.1007/s13566-015-0222-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of normal tissue radiation injury: evidence from rat radiation nephropathy models

Abstract: Normal tissue radiation injury is a common complication of radiation therapy and is also a major concern after accidental or belligerent radiation exposure, and until recently, it was deemed untreatable. Both experimental and clinical evidence now show that radiation injury can be alleviated by agents started after irradiation but before manifestation of that injury (a therapeutic approach called Bmitigation^). Mitigation of normal tissue injuries would improve clinical radiation therapy, and it will be an ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…In preparation for studies of the mitigation efficacy of dietary antioxidants we placed rats on this type of diet, specifically a modified version of AIN-76A. In a radiation nephropathy model (Cohen et al 2015) we found that, compared to our standard diet (Teklad 8904), use of the AIN-76A diet after irradiation significantly decreased the incidence and severity of radiation nephropathy. Further studies were then conducted to confirm this unexpected effect, to attempt to determine its mechanistic basis, and to test whether the effect also extended to radiation pneumonitis.…”
Section: Introductionmentioning
confidence: 99%
“…In preparation for studies of the mitigation efficacy of dietary antioxidants we placed rats on this type of diet, specifically a modified version of AIN-76A. In a radiation nephropathy model (Cohen et al 2015) we found that, compared to our standard diet (Teklad 8904), use of the AIN-76A diet after irradiation significantly decreased the incidence and severity of radiation nephropathy. Further studies were then conducted to confirm this unexpected effect, to attempt to determine its mechanistic basis, and to test whether the effect also extended to radiation pneumonitis.…”
Section: Introductionmentioning
confidence: 99%